Universal Systems Language: Lessons Learned from Apollo. - Hamilton, Margaret H.; Hackler, William R. (Computer (00189162), 2008)
The article focuses on universal systems language (USL). USL is based on systems theory and is significantly derived from the Apollo onboard flight software effort. It's purpose has been to provide solutions to problem viewed as next to impossible to solve with traditional methods. According to users, USL thinks in terms of system-oriented objects (SOOs) and system-driven models. The authors list a set of objectives about how they designed objectives for USL. The article mentions the development of the Apollo flight software.